Single‐breath xenon polarization transfer contrast (SB‐XTC): Implementation and initial results in healthy humans. Issue 2 (25th September 2012) - Muradyan, Iga; Butler, James P.; Dabaghyan, Mikayel; Hrovat, Mirko; Dregely, Isabel; Ruset, Iulian; Topulos, George P.; Frederick, Eric; Hatabu, Hiroto; Hersman, William F.; Patz, Samuel
Abstract Purpose: To implement and characterize a single‐breath xenon transfer contrast (SB‐XTC) method to assess the fractional diffusive gas transport F in the lung: to study the dependence of F and its uniformity as a function of lung volume; to estimate local alveolar surface area per unit gas volume SA/VGas from multiple diffusion time measurements of F; to evaluate the reproducibility of the measurements and the necessity of B1 correction in cases of centric and sequential encoding. Materials and Methods: In SB‐XTC three or four gradient echo images separated by inversion/saturation pulses were collected during a breath‐hold in eight healthy volunteers, allowing the mapping of F (thus SA/VGas) and correction for other contributions such as T1 relaxation, RF depletion and B1 inhomogeneity from inherently registered data. Results: Regional values of F and its distribution were obtained; both the mean value and heterogeneity of F increased with the decrease of lung volume. Higher values of F in the bases of the lungs in supine position were observed at lower volumes in all volunteers. Local SA/VGas (with a mean ± standard deviation of <overline>SA/VGas</overline> = 89±30 cm−1) was estimated in vivo near functional residual capacity. Calibration of SB‐XTC on phantoms highlighted the necessity for B1 corrections when k‐space is traversed sequentially; with centric ordering B1 distribution correction is dispensable. Conclusion: The SB‐XTC technique is implemented and validated for in vivo measurements of local SA/VGas. J. Magn. Reson. Imaging 2013;37:457–470. © 2012 Wiley Periodicals, Inc.